Knowledge, attitudes and practices among patients with periodontal disease toward disease management - Zhao, Siyu; Wu, Yanyun (Frontiers in Public Health, 2024)
IntroductionPeriodontal disease is a common chronic inflammatory condition that affects oral health and carries broader public health implications. This study aimed to assess the levels of knowledge, attitudes and practices (KAP) among patients with periodontal disease toward disease management.MethodsThis cross-sectional web-based study was conducted between March 2022 and March 2023. A self-administered questionnaire was designed to evaluate KAP toward disease management.ResultsA total of 514 questionnaires were collected. Among the patients, 313 (60.89%) of them were female, 309 (60.12%) resided in urban areas and 130 (25.29%) reported having severe periodontal disease. The mean scores of knowledge, attitudes and practices were 3.05 ± 2.03 (possible range: 0–8), 18.71 ± 3.64 (possible range: 6–30), and 14.85 ± 3.63 (possible range: 5–25), respectively. The knowledge item with highest correctness rate was the link between periodontal disease and systemic health (60.70%), while the lowest correctness rate was seen for understanding disease classification (36.96%). Pearson’s analysis revealed positive correlations between knowledge and attitude (r = 0.31, p < 0.001), knowledge and practices (r = 0.23, p < 0.001) attitudes, as well as attitudes and practices (r = 0.17, p < 0.001). Multivariate logistic regression analysis showed that knowledge (OR = 1.30, 95% CI: 1.14–1.49, p < 0.001), age ≥ 33 years old (OR = 0.33, 95% CI: 0.18–0.62, p = 0.001), housewife/househusband (OR = 0.41, 95% CI: 0.17–0.95, p = 0.037) and student (OR = 0.43, 95% CI: 0.20–0.92, p = 0.029) were independently associated with practices.ConclusionPatients with periodontal disease had insufficient knowledge, negative attitudes, and passive practices toward disease management. Further efforts could be directed toward enhancing patient education on periodontal disease to improve knowledge, thereby positively influencing attitudes and disease management practices.